To solve the quadratic equation \( x^2 - 16x - 13 = 14 \) by completing the square, first, we need to rearrange the equation into a standard form:
-
Subtract 14 from both sides:
\[ x^2 - 16x - 13 - 14 = 0 \]
This simplifies to:
\[ x^2 - 16x - 27 = 0 \]
-
Now, let's complete the square. We want to express the quadratic in the form \( (x - p)^2 = q \).
-
First, take the coefficient of \( x \), which is \(-16\), halve it, and then square it:
\[ \left( \frac{-16}{2} \right)^2 = (-8)^2 = 64 \]
-
Next, add and subtract \( 64 \) to the left-hand side of the equation:
\[ x^2 - 16x + 64 - 64 - 27 = 0 \]
This can be rearranged to:
\[ (x - 8)^2 - 91 = 0 \]
-
Now isolate the squared term:
\[ (x - 8)^2 = 91 \]
-
Take the square root of both sides:
\[ x - 8 = \pm \sqrt{91} \]
-
Finally, solve for \( x \):
\[ x = 8 \pm \sqrt{91} \]
Thus, the two values that solve the equation are:
\[ x = 8 + \sqrt{91} \quad \text{and} \quad x = 8 - \sqrt{91} \]